E-Commerce, Financial Technology, and MSME Development: the Moderating Role of Digital Literacy in Islamic Economics - Anwar Sadat; Muhammad Syukri Albani Nasution; Muhammad Irwan Padli Nasution (LP2M IAIN Palopo, 2026)
Purpose: This study examines the direct effects of e-commerce, financial technology, and digital literacy on MSME development in Medan City, tests digital literacy as a moderator, and interprets the findings from an Islamic economic perspective. Methods: A quantitative cross-sectional survey involved 85 digitally active MSME owners or operators purposively selected from a population of 38,343 businesses. Five-point Likert data were analyzed using partial least squares structural equation modeling (PLS-SEM). Results: E-commerce (β = .256; p = .013), financial technology (β = .359; p = .001), and digital literacy (β = .359; p < .001) each had positive direct effects. The model explained 73.3% of MSME-development variance. Digital literacy did not moderate the financial-technology relationship (β = .005; p = .959) or the e-commerce relationship (β = -.057; p = .592). Implications: Digital literacy operates primarily as a direct business capability. MSME support should combine e-commerce optimization, secure digital finance, and Sharia-compliant digital-literacy development based on transparency, mutual consent, justice, and avoidance of riba, gharar, maysir, tadlis, and prohibited transactions.